2010
DOI: 10.2320/matertrans.m2009402
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Properties of Titanium in PEFC Bipolar Plate Environments

Abstract: In order to assess the applicability of titanium as a bipolar plate for polymer electrolyte fuel cells (PEFCs), the electrochemical surface characteristics of commercially available pure titanium were examined in simulated PEFC conditions. The results of the electrochemical tests showed that the cathode operating potential of PEFC, 0.64 V (vs. Ag/AgCl(3.33 kmolÁm À3 KCl)), lay in the anodic passivation region for titanium. The operating potential of the PEFC anode, À0:36 V, lay in the cathodic region or the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…In Figure 10, identical cathodic protection behaviour characterised by negative corrosion currents is observed for CoBlast Ti and bare Ti samples indicating that dissolution rate is reduced. This electrochemical behaviour of modified and bare Ti grade (V) alloy is in agreement with previous studies on other Ti alloys in PEM fuel cell environments and is attributed to the low applied potential of −0.1V which facilitates the formation of a stable oxide layer after an initial dissolution of the preexisting layer [13,14].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In Figure 10, identical cathodic protection behaviour characterised by negative corrosion currents is observed for CoBlast Ti and bare Ti samples indicating that dissolution rate is reduced. This electrochemical behaviour of modified and bare Ti grade (V) alloy is in agreement with previous studies on other Ti alloys in PEM fuel cell environments and is attributed to the low applied potential of −0.1V which facilitates the formation of a stable oxide layer after an initial dissolution of the preexisting layer [13,14].…”
Section: Resultssupporting
confidence: 91%
“…Recently, few studies have attempted to explain the corrosion phenomena of Ti and its alloys in PEM fuel cell environments. Soma et al [13] found that the air-formed surface oxide on Ti becomes unstable when exposed to PEM fuel cell anodic conditions thereby resulting in high anodic currents at the inception of polarisation. This behaviour of Ti in anodic conditions was attributed to the low applied potential of −0.1 V. The preexisting passive layer however rapidly dissolves and gives way to a newly formed oxide layer which cathodically protects the metal.…”
Section: Introductionmentioning
confidence: 99%
“…23) Meanwhile, separators and other materials used in PEFCs have been evaluated under many test conditions: 3,8,23,24,27,31) Conditions include adding 2-15 ppm of fluoride ions, and taking the influence of the electric potential, oxygen on the cathode side, and hydrogen on the anode side into account under the operating conditions of the PEFC; and the pH is 0-4 for such conditions. Among these tests, Soma et al 24) polarized titanium on the anode side in a sulfuric acid aqueous solution with a pH of 2.7 and a fluoride ion concentration of approximately 2 ppm at 80°C for 72 h. Based on the surface form, they showed that a film grew by the deposition of TiO 2 , a mechanism in which Ti dissolves and TiO 2 is deposited. This phenomenon and mechanism are very similar to the discoloration phenomenon reported by Kaneko et al, 20,22) who showed that when titanium was exposed to a sulfuric acid aqueous solution with a pH of 4.5 or less, an oxide film (deposited TiO 2 ) grew.…”
Section: Sulfuric Acid Aqueous Solution Exposure Test Andmentioning
confidence: 99%
“…16,[20][21][22] That is, under the environment in which PEFCs are used, titanium oxide films may grow, which may increase the contact resistance. 23,24) To solve the above problem, Kimura et al 25) reported that pickling titanium sheets on which there is no TiC, TiN, or Ti 2 N with nitric hydrofluoric acid and then immersing them in a concentrated aqueous solution of nitric acid (acid with oxidizability) (hereafter, nitric acid immersion) significantly enhances the color fastness in a sulfuric acid aqueous solution environment (immersion in a sulfuric acid aqueous solution with a pH of 4 at 60°C). The color difference, which is an indicator of the level of film growth, and the corresponding discoloration decreased from over 10 to less than 2.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that SnO2 exhibits high conductivity among various metal oxides, and high durability against potential cycling (1)(2)(3)(4)(5)(6). TiOx with high potential stability is naturally formed on the outermost surface of the titanium metal (7,8).…”
Section: Introductionmentioning
confidence: 99%